Promoting the study of plant taxonomy: a new species of Anthurium (Araceae) named by students from the University of Panama - Ortiz, Orlando O.; Croat, Thomas B.; Espinosa, Hilario; Baldini, Riccardo M. (Phytotaxa, 2020)
Currently in Panama, as in other parts of the world, there is little interest in taxonomy, both at the educational and research levels. In order to increase awareness and research interest in plant taxonomy amongst botany majors, we involved a cohort of college-level students of the University of Panama’s Biology School in the process of naming a yet-to-be described species of Anthurium (Araceae), engaging them in all aspects of taxonomy including the process of proposing a new species to the scientific community. With their help, we hereby describe a new species we named Anthurium oistophyllum, with descriptions and illustrations based upon photographs of the vegetative and reproductive structures taken from live material.